Machine Retrograde Perfusion of Deceased Donor Kidneys: A Prospective Study - Zeng, Jun; Jia, ZiHao; Lin, Tao; Song, TuRun (Frontiers in Medicine, 2021)
Objective: To maximize the utilization of potential kidneys, improving perfusion and preservation techniques is necessary. Methods: We investigated the safety and efficacy of retrograde machine perfusion of kidneys from deceased donors. A total of 30 kidneys were included and all the grafts were preserved in the Kidney Transporter machines. A total of 15 kidneys that received retrograde perfusion (RP) were selected as the RP group (n = 15) and their counterparts received standard antegrade perfusion (AP) as the control group (n = 15). Results: All the recipients were followed up for 6 months. Renal resistance in the RP group remained stable during the perfusion. There was no primary nonfunction. No difference in the incidence of delayed graft function was found in both groups (3 in RP vs. 2 in AP, p = 0.62). The RP group had lower serum creatinine (RP vs. AP, 102.20 vs. 138.67, p = 0.05) and blood urea nitrogen (RP vs. AP, 6.44 vs. 8.71, p = 0.05) than that in the AP group at 6 months. Both the groups had comparable estimated glomerular filtration rate and cystatin C within 6 months. Conclusion: This novel technique may be an effective and safe alternative for kidney preservation.